The Effect of Conjugation Wheel Interactive PowerPoint for Learning French Verbs in Grade XI 85 Senior High School in West Jakarta - Sukma Ramadhan; Yonathan Winardi (Franconesia, 2024)
This article aims to elaborate the effect of a newly developed learning media as a group of French language teachers in Jakarta affirmed the need of a learning media in the form of interactive powerpoint that can shape students’ understanding of French conjugation verbs. The researchers then decided to develop conjugation wheel interactive powerpoint (CWIPPT) using ADDIE model and eventually test its effectiveness for grade XI students. A quasi-experimental research method was used, specifically the non-equivalent control group design and two grade XI classes in senior high school 85 in West Jakarta were willing to participate as control and experiment groups. A validated pre and post tests were used to measure the increase of students understanding of French conjugation verbs. The results show that the control group had an N-Gain of 0.26, while the experimental group had 0.81, indicating a much bigger improvement in the experimental group. It is recommended French teachers use CWIPPT and an apps of it to be developed so that more students can use and get the benefits of it.